KEKUATAN KINERJA KEUANGAN DALAM MENINGKATKAN HARGA SAHAM SYARIAH - Ahmad Muzaqi Mu'min; Mira Rahmi (Veteran Economics, Management, & Accounting Review, 2023)
This study aims to analyze how much influence ROE, EPS, and PER have on Islamic stock prices with inflation as a moderating variable. This research method is quantitative using secondary data and panel data regression analysis method. The research findings confirm that ROE and PER have a significant effect on stock prices directly, while EPS does not have a significant effect on stock prices directly. To test inflation as a moderation is not able to moderate the relationship between the ROE, EPS, and PER variables indirectly. For further research it is recommended to use the addition of independent variables other than those used in this study, as well as taking other population and sector samples. Keywords: efficiency of corporate tax burden; the role of a tax consultant; tax management   Abstrak Suatu pilihan untuk masyarakat untuk berinvestasi pada pasar modal, salah satunya Investasi saham pada pasar modal syariah merupakan pilihan yang sangat membantu untuk kaum muslim diantara pasar modal lain yang tidak terjamin perputaran keuangannya dalam syariat islam. Selain itu, untuk menjamin keuntungan yang akan didapatkan, perlunya analisis dalam melihat bagaimana kinerja keuangan perusahaan mempengaruhi harga sahamnya. Penelitian ini bertujuan untuk menganalisis seberapa besar pengaruh yang dihasilkan ROE, EPS, dan PER terhadap Harga Saham Syariah dengan Inflasi sebagai variabel moderasi. Metode penelitian ini adalah kuantitatif dengan menggunakan data sekunder dan metode analisis regresi data panel. Temuan penelitian mengkonfirmasi bahwa ROE dan PER memiliki pengaruh signifikan terhadah harga saham secara langsung, sementara EPS tidak berpengaruh signifikan terhadap harga saham secara langsung. Untuk pengujian inflasi sebagai moderasi tidak mampu memoderasi hubungan antara variabel ROE, EPS, dan PER secara tidak langsung. Bagi penelitian selanjutnya disarankan untuk menggunakan penambahan variabel-variabel independent selain yang digunakan pada penelitian ini, serta mengambil populasi dan sampel sektor lain. Kata Kunci: ROE, EPS, PER, harga saham, inflasi   Abstract  An option for people to invest in the capital market, one of which is investing in shares in the Islamic capital market is a very helpful option for Muslims among other capital markets whose financial turnover is not guaranteed in Islamic law. In addition, to guarantee the benefits that will be obtained, an analysis is needed to see how the company's financial performance affects its share price. This study aims to analyze how much influence ROE, EPS, and PER have on Islamic stock prices with inflation as a moderating variable. This research method is quantitative using secondary data and panel data regression analysis method. The research findings confirm that ROE and PER have a significant effect on stock prices directly, while EPS does not have a significant effect on stock prices directly. To test inflation as a moderation is not able to moderate the relationship between the ROE, EPS, and PER variables indirectly. For further research it is recommended to use the addition of independent variables other than those used in this study, as well as taking other population and sector samples.  Keywords: ROE, EPS, PER, stock prices, inflation